Keefektifan Model Contextual Teaching And Learning (CTL) dan Model Think Pair Share (TPS) dengan Media Puzzle dalam Pembelajaran Menulis Surat Dinas Pada Siswa Kelas VII SMP - Prihatini, Ika Aprilia; Utami, Santi Pratiwi Tri (LP3 Universitas Negeri Semarang, 2020)
Penelitian ini bertujuan untuk mengetahui keefektifan model contextual teaching and learning (CTL), keefektifan model think pair share (TPS), dan mengetahui manakah yang lebih efektif di antara model contextual teaching and learning (CTL) dan model think pair share (TPS) dalam pembelajaran menulis surat dinas pada siswa kelas VII Sekolah Menengah Pertama (SMP). Jenis penelitian ini adalah quasi experimental design dan menggunakan nonequivalent control group design. Hasil penelitian ini menunjukkan bahwa pembelajaran menulis surat dinas pada siswa kelas VII smp lebih efektif diterapkan menggunakan model contextual teaching and learning (CTL), dibandingkan model think pair share (TPS) dengan nilai hasil rata-rata posttest 90,31 80,94 dan nilai signifikansi 0,002 0,05This study aims to determine the effectiveness of the contextual teaching and learning (CTL) model, the effectiveness of the think pair share (TPS) model, and find out which is more effective between the contextual teaching and learning (CTL) model and the think pair share (TPS) model in learning write official letters to grade VII students of junior high school. This type of research is a quasi experimental design and uses nonequivalent control group design. The results of this study indicate that the contextual teaching and learning (CTL) model is effectively applied in learning to write official letters, the effective think pair share (TPS) model is applied in learning to write official letters, and the contextual teaching and learning (CTL) model is more effective than the application of the model think pair share (TPS) in learning to write official letters with puzzle media on grade VII junior high school students with an average posttest score of 90.31 80.94 and a significance value of 0.002 0.05.